A cross sectional study on the bacteriologic pattern of chronic otitis media and its antibiotic sensitivity - C., Ramya Shree; S., Prabakaran; S., Rajasekaran; K., Priya; R. B., Namasivaya Navin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media is the commonest middle ear and mastoid cavity disease, which has the tendency of causing morbidity to the patients ranging from deafness to intracranial complications. Hence this study was done to identify the local bacteriological pattern and its antibiotic sensitivity for treating them with appropriate antibiotic therapy. Methods: This cross-sectional study was done retrospectively with reports of culture and sensitivity of chronic otitis media from microbiology department. The sample was sent from the department of otorhinolaryngology in Chettinad hospital and research institute, Chennai, during the period from January 2018 to January 2020. Results: On assessing about 188 reports, 17 patients had no growth of organism. The commonest organism isolated was Pseudomonas species (33.0%) which was sensitive to imipenem (96.8%), followed by Staphylococcus (28.7%) which was sensitive to linezolid and teicoplanin (98.1%). Conclusions: The study concludes imipenem for Pseudomonas species and linezolid/teicoplanin for Staphylococcus. The appropriate and adequate antibiotic therapy is always recommended for chronic otitis media to avoid complications.